Energy cooperation between Kazakhstan and China under “One Belt and One Road”: current state, challenges and perspectives - Binghan , Du; Juman , J.; Khamzayeva, A.V.; Xuan, Zhai (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of this study is to examine the opportunities and challenges of energy cooperation between Kazakhstan and China under “One Belt and One Road” (OBOR) using SWOT analysis and to propose optimization recommendations for upcoming energy cooperation projects between the two countries. Methods: The methodology used in this study includes comparative data analysis and statistical analysis for quantitative data. A mind map was created using SWOT analysis to visualize the opportunities and challenges of energy cooperation between China and Kazakhstan. Findings: The results of the study indicate that the complementarity of the energy structures of China and Kazakhstan is a motivation for energy cooperation. The risks of energy cooperation between China and Kazakhstan are mainly due to the instability of the international energy market. Energy cooperation under OBOR Initiative can help to promote the development of their economies. Conclusions: According to the research, energy cooperation is one of the most important components of the OBOR Initiative. Through energy cooperation, Kazakhstan and China can realize their plans for the development of renewable energy sources as much as possible based on ensuring energy security.